EVALUATION OF ACUTE AND SUB-ACUTE ORAL TOXICITY OF CLINACANTHUS NUTANS LEAVES EXTRACT IN MICE - GIANG, TRAN THI LINH; THACH, LE KIM; LINH, LE NGUYEN TU; DAO, VU QUANG; BEN, TRINH THI; THACH, BUI DINH (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study aimed to evaluate acute and sub-acute oral toxicity of ethanol extract of Clinacanthus nutans leaves in Swiss mice. Methods: Acute oral toxicity study was performed as per OECD-423 guidelines. Sub-acute oral toxicity study was performed as per OECD-407 guidelines. The extract was dissolved in 10% dimethyl sulfoxide and administered orally, while the control group received only the vehicle. Results: The acute oral toxicity test on mice showed that this extract was well tolerated up to LD50 5000 mg/kg body weight/day oral dosage level and non-toxic to mice under the present experimental conditions. The sub-acute toxicity study was carried out on mice with the oral dosage of the extract from 100 mg/kg–500 mg/kg body weight/day and 5000 mg/kg body weight/day for 28 d. The results showed that this extract did not induce death or adverse effects in activity, feed consumption or body weight gain. There were not significant changes in heamotological and biochemical parameters between control and experiment groups. Conclusion: Thus, Clinacanthus nutans leaf has a very low toxicity value.